Integrated control of Sericea lespedeza in Kansas - Walter H. Fick (Kansas Agricultural Experiment Station Research Reports, 2000)
Two experiments were conducted near Maple Hill, KS in 1998 to compare the effectiveness of herbicides and mowing used alone and in combination for control of sericea lespedeza (Lespedeza cuneata). Remedy® at 0.5 lb/acre was more effective when applied during the vegetative growth stage (>87%) than during flowering or seed production. Ally® at 0.4 oz/acre provided control equivalent to Remedy and was equally effective at both the vegetative and bloom stages. Both herbicides provided less than 60% control when applied during seed production. A single mowing on July 8 was not effective. Mowing followed in 6 weeks by Remedy at 0.25 lb/acre or Ally at 0.2 oz/acre provided control equivalent to that with the higher rates of Remedy or Ally alone.
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Sericea lespedeza; Integrated control; Remedy®; Ally®; Rangeland